Norwegian kidney biopsy biobank (NorKiBB): organization, baseline characteristics, and generalizability of a low-cost national biobank - Marius Altern Øvrehus; Knut Asbjørn; Rise Langlo; Sabine Leh; Øystein Eikrem; Solfrid Romundstad; Håvard Aksnes; Ingjerd Wangensteen Manner; Christian Aalborg; Marit D. Solbu; Lasse G. Gøransson; Hans-Peter Marti; et al. (BMC Nephrology, 2025)
Abstract Background Biobanks that hold blood, urine and kidney tissue are key for translational nephrology research but are few and have limited availability. We describe the organization, baseline characteristics, and generalizability of a low-cost national biobank. Materials and methods Eight Norwegian hospitals participated in this multi-center, prospective cohort study and biobank initiative. Patients referred for routine clinical native kidney biopsies were eligible for inclusion, starting September 2020. Extensive information on medical history and risk factors were collected into an encrypted on-line database by the treating nephrologist. A comprehensive standardized panel of blood and urine tests were analyzed in the clinical routine and registered along with the full histology report. Extra urine and blood samples were collected, aliquoted and prepared locally within two hours, frozen at -80 C, and later sent to a central government-funded biorepository together with remaining kidney biopsy material. Results By September 2023, a total of 633 patients were included out of 1050 eligible patients. Mean age was 52.6 years (SD 18.7), 384 (61%) were men, and participants displayed a wide spectrum of kidney disease with mean estimated glomerular filtration rate (eGFR) 53 mL/min/1.73m2. The most frequent biopsy indications were progressive chronic kidney disease (CKD) of unknown cause, acute kidney disease, and isolated hematuria/proteinuria. The most frequent diagnoses were IgA nephropathy (21%), arterionephrosclerosis (13%), and diabetes nephropathy (9%). Biopsy indications and diagnoses were similar to the spectrum typically seen in Norway and other western countries, and similar population level kidney health measures were demonstrated for Norway, United Kingdom, and USA. Discussion We demonstrate the feasibility of establishing a large national kidney biopsy biobank across a variety of clinical and histopathologic diagnoses. Blood and urine were stored, accompanied by kidney tissue, at a moderate cost due to a combination of a dedicated nephrology workforce, routine clinical care, and established biobank facilities.